The Changes in Vast Mangrove Area of Pantai Air Telang Protected Forest Banyuasin District using Landsat Imagery Data Time Series - Vina , Vina Fitriana; Rujito , Rujito Agus Suwignyo; Siti , Siti Fauziyah (Forestry Department, University of Muhammadiyah Makassar, 2017)
This study aimed to obtain data about far-reaching changes on the total area of mangrove at Air Telang Beach Protected Forest through the interpretation of Landsat 7 imagery data using open source software (Ilwis 2000) in years 2000, 2003, 2006, 2009 and 2012. In the first phase, mangrove identification was conducted through cropped imagery data based on the research area which is path 124 raw 62 using RGB543 composite band. Then, mangrove and non-mangrove area are separated using unsupervised classification method. The next phase, mangrove density analysis is directed by applying NDVI formula. The results showed that the total area of mangrove has decreased over a period of 12 years by 10.72 % of total mangrove area on 2000 (7,968.54 ha) with 7,147.12 on 2012. Vegetation Index analysis shows high density mangrove is dominated although it continues to decrease, followed by increasing mangrove area with medium density.